Extreme animal rumble : 5 books in 1! - Pallotta, Jerry; Bolster, Rob; Pallotta, Jerry; Pallotta, Jerry; Pallotta, Jerry; Pallotta, Jerry; Pallotta, Jerry (New York, NY : Scholastic, Inc., 2021)
What would happen if sixteen sharks met in a tournament? What if the jungle's fiercest creatures battled it out? Which dinosaur is the strongest of them all?
Ultimate ocean rumble -- Ultimate bug rumble -- Ultimate dinosaur rumble -- Ultimate jungle rumble-- Ultimate shark rumble -- Rewrite the brackets!
Grade 3.
1st-3rd graders.
Keywords: Competition (Biology) -- Juvenile literature; Contests -- Juvenile literature; Marine animals -- Juvenile literature; Insects -- Juvenile literature; Dinosaurs -- Juvenile literature; Jungle animals -- Juvenile literature; Sharks -- Juvenile literature; Competition (Biology); Contests; Marine animals; Insects; Dinosaurs; Jungle animals; Sharks